Microstrip Patch Antenna for Global Positioning System based Application using Dual Band Frequency and its Analysis - Mandeep Singh Heer , Dr. Vikrant Sharma (International Journal of Advanced Science and Technology, 2020)
A novel dual-frequency geometry of a single-layer single-feed rectangular microstrip patch antenna is investigated in this communication. The designed antenna is functionable in the range of 3 to 6 GHz for GPS usage. The proposed antenna not only resonates efficiently at two nearly spaced frequencies (3.39 GHz and 5.34 GHz) but also offers improved bandwidth (13%) in comparison with a conventional rectangular microstrip antenna, optimization of a ground plane dimensions is about 4% achieved.